Analisis Karakter Toleransi Tema Indahnya Keragaman Di Negeriku Pada Buku Siswa Kelas IV SD - Indri Triyani Putri; Dyah Lyesmaya; Arsyi Rizqia Amalia (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
This study aims to analyze the indicators of tolerance character contained in the material for the fourth grade students of SD Tema The Beauty of Diversity in My Country. The type of research used is descriptive qualitative. The research method used was content analysis. The data taken in this study were the load of tolerance characters in the sentences contained in the student books on social studies material. The subject used in this research is the book of the fourth grade students of the 2013 curriculum at the theme The Beauty of Diversity in My Country. The data analysis technique is done by reducing data, presenting the data which is divided into two stages, namely data classification, data description and interpretation, and drawing conclusions. The results showed that all indicators of tolerance character contained in textbook learning materials, the distribution of tolerance character indicators in learning materials was evenly distributed, except for the anti-phobia sub-indicators contained in the aspect of peace (not included in theme 7), techniques for integrating tolerance character indicators with material learning is carried out through reading texts contained in student books.